A Dicationic Bismuth(III) Lewis Acid: Catalytic Hydrosilylation of Olefins. Issue 28 (28th June 2019) - Balasubramaniam, Selvakumar; Kumar, Sandeep; Andrews, Alex P.; Varghese, Babu; Jemmis, Eluvathingal D.; Venugopal, Ajay
Abstract: Invited for the cover of this issue is Ajay Venugopal from the Indian Institute of Science Education and Research Thiruvananthapuram. The cover image shows dication [Tp Me2 Bi] 2+ catalyzing olefin hydrosilylation under mild conditions. Abstract : Our exploration on this bismuth dication has provided a glimpse of how "soft" bismuth can be made to exhibit hard electrophilic properties … Read more about the story behind the cover in the Cover Profile and about the research itself in the Communication by A. Venugopal et al.